Vibration Characteristics and Simulation Verification of the Dual-Rotor System for Aeroengines with Rub-Impact Coupling Faults - Pingping Ma; Mingxin Shan; Jingyu Zhai; Hao Zhang; Qingkai Han (Shock and Vibration)
To study the rub-impact fault between the dynamic and static parts of the rotor system of aeroengines, the dual-rotor system of a typical aeroengine is introduced and taken as the research object. The analytical kinetic model is established based on the Lagrange equation considering the structural characteristics of the dual-rotor system, the coupling effect of the intermediate bearing, and the rub-impact fault between the high-pressure turbine disc and the casing. The dynamic characteristics of the dual-rotor system under the rub-impact fault are analyzed, and the change rule of the rub-impact shape is obtained. The vibration coupling and transfer among the high-pressure rotor and the low-pressure rotor are revealed. The influence of the unbalanced position and the speed of high and low rotors on the vibration response of the dual rotor is obtained. The sensitivity of the vibration response of the dual rotor at different test points to rub-impact stiffness, clearance, and friction coefficient is compared. The simulation model is established based on the rigid-flexible coupling multibody dynamic simulation platform. The analytical results and simulation results are compared, which have a good consistency. The theoretical research can deepen the understanding of the nature and law of aeroengine rotor operation, expose the possible faults and design defects, greatly improve the development efficiency and quality, reduce repeated physical tests, reduce the development risk and cost, and accelerate the development process. This study can provide a theoretical basis for the monitoring and diagnosis of engine rub-impact faults and provide theoretical and practical reference for the establishment of the vibration fault test and analysis method system.